2015
DOI: 10.1007/698_2015_346
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation with Treated Wastewater: Potential Impacts on Microbial Function and Diversity in Agricultural Soils

Abstract: The reuse of treated wastewater could be a promising measure to attenuate the water scarcity burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 150 publications
(132 reference statements)
1
8
0
Order By: Relevance
“…Treated wastewater may also increase abundance of soil microbes, specifically fungal and bacterial community compositions [325], and change the ammonia-oxidizing bacteria in soils [326,327]. The significant microbiological threats that were related to the implementation of wastewater irrigation in agriculture are specific towards disruption of soil's native microbial populations and the impact on their functional process [328].…”
Section: Irrigation Watermentioning
confidence: 99%
“…Treated wastewater may also increase abundance of soil microbes, specifically fungal and bacterial community compositions [325], and change the ammonia-oxidizing bacteria in soils [326,327]. The significant microbiological threats that were related to the implementation of wastewater irrigation in agriculture are specific towards disruption of soil's native microbial populations and the impact on their functional process [328].…”
Section: Irrigation Watermentioning
confidence: 99%
“…Ruiz et al [29] found that salinity reduced leaf Mg concentration in citrus. Variable results may be produced by the compounds in saline water and their concentrations, the duration of irrigation, and the species and varieties of crops irrigated [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous microorganisms in a given ecosystem are the principal participants and drivers of biogeochemical cycling of elements and are sensitive indicators of a given ecosystem change (Song et al, 2013). The direct microbiological risks associated with the use of drainage water in agricultural irrigation were mainly the disturbance of the indigenous microbial communities in soil ecosystems (Lopes et al, 2015). Nevertheless, our understanding of these aspects has much room for improving.…”
Section: Et Al (2005)mentioning
confidence: 99%